The effects of fungicides on the microbiology and biochemistry of soils - Wainwright, Milton (1974)
A study was made of the effects of a wide range of modern fungicides on the microbiology and biochemistry of soils. The addition of fungicides to laboratory incubated soils led to marked changes in the soil microbial equilibrium. Initially fungal potential was decreased, but soon recovered to exceed that of the control at the end of 28 days. Bacterial numbers on the other hand increased dramatically following treatment. Similar changes were seen in field soils which had been treated with fungicides. The response of the cellulolytic fungal flora to field treatment with fungicides was also studied. Changes in the pattern of recolonization occurred, with species such as T. koningii, and P. nigricans becoming dominant. Cellulolytic fungi were largely insensitive to the addition of fungicides to their growth medium. Marked changes in the mineralization of nitrogen followed fungicide treatment. In the field all the fungicides used inhibited nitrification to a greater or lesser extent while levels of the ammonium ion were increased. Similar changes were seen in laboratory incubated soils. Here treatment with high concentrations of fungicides led to nitrification-inhibition while an increase in nitrate production often followed treatment with low concentrations. The amounts of ammonium-N in these soils increased dramatically following treatment. Towards the end of the incubation period (28 days) low concentrations of fungicides led to increases in the total free amino-acid-N content in soil, while the converse was true of high concentrations. Addition of fungicides also led to qualitative changes in the free amino acid content of soils. Increases were seen in certain metal ions including K. Na, Mn and Zn in fungicide treated soils. A compound exhibiting auxin activity was extracted and characterised as 3-Indole-pyruvic acid. However the exact origin of this compound is unknown. It seems likely that it was an extraction artefact since IPyA is highly unstable under the extraction conditions which were employed. The potential for soil auxin activity existed however and was increased two-fold by the addition of the fungicide Captan to the soil. Finally the possible effects of these changes on soil fertility are discussed, particularly in relation to the increased growth response phenomenon, associated with the partial sterilization of soil.